Success of extracorporeal shock wave lithotripsy and ERCP in symptomatic pancreatic duct stones: a systematic review and meta-analysis - van Huijgevoort, Nadine C.M.; Veld, Joyce V.; Fockens, Paul; Besselink, Marc G.; Boermeester, Marja A.; Arvanitakis, Marianna; van Hooft, Jeanin E. (Endoscopy International Open, 2020)
Background and study aims Pain is the most frequent and dominant symptom of chronic pancreatitis. Currently, these patients are treated using a step-up approach, including analgesics and lifestyle adjustments, endoscopic, and eventually surgical treatment. Extracorporeal shock wave lithotripsy (ESWL) is indicated after failure of the first step in patients with symptomatic intraductal stones larger than 5 mm in the head or body of the pancreas. To assess the complete ductal clearance rate and pain relief after ESWL in patients with symptomatic chronic pancreatitis with pancreatic duct stones, a systematic review and meta-analysis was performed.Patients and methods A systematic literature search from January 2000 to December 2018 was performed in PubMed, the Cochrane Library, and EMBASE for studies on ductal clearance rate of ESWL in patients with symptomatic chronic pancreatitis with pancreatic duct stones.Results After screening 486 studies, 22 studies with 3868 patients with chronic pancreatitis undergoing ESWL for pancreatic duct stones were included. The pooled proportion of patients with complete ductal clearance was 69.8 % (95 % CI 63.8–75.5). The pooled proportion of complete absence of pain during follow-up was 64.2 % (95 % CI 57.5–70.6). Complete stone fragmentation was 86.3 % (95 % CI 76.0–94.0). Post-procedural pancreatitis and cholangitis occurred in 4.0 % (95 % CI 2.5–5.8) and 0.5 % (95 % CI 0.2–0.9), respectively.Conclusion Treatment with ESWL results in complete ductal clearance rate in a majority of patients, resulting in absence of pain during follow up in over half of patients with symptomatic chronic pancreatitis caused by obstructing pancreatic duct stones.